In every tiny grain of sand : a child's book of prayers and praise - Lindbergh, Reeve; Davenier, Christine (Cambridge, Mass. : Candlewick Press, 2000)
A collection of inspirational poems, prayers, and other writings grouped, "For the day, For the home, For the earth, and For the night."
Keywords: Children -- Prayers and devotions; Prayer books and devotions